Результати інвентаризації видів роду Spiraea L. із колекції дендропарку “Олександрія” НАН України - Kalashnikova, L.V.; Bonyuk, Z.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to study of the taxonomic composition of the genus Spiraea L. of the dendropark Oleksandria collection according to the inventory data of 2018. Material and methods. Objects: species, hybrids and forms of the genus Spiraea from collection of Dendropark Olexandria, created by the method of the F. Rusanov generic complex (1971) during 1950–2010 in plots “Fruticetum”, “Rare plants” and planted in the landscapes compositions of the Dendropark. The history of the formation of the collection was studied by catalogs of tree plants of Dendropark Olexandria in 1996 and 2013. The taxonomic composition was analyzed according to the monograph “Tavolgi” (Spiraea L.) (2008) and “The check list of Dendroexotics of Ukraine” (2016). The degree of winter-hardiness is measured by the S. Sokolov 8-point scale (1957), drought-resistance – by the S. Pyatnitsky 6-point scale (1961). Results. According to the catalog of tree plants in 1996, the collection of taxa of the genus Spiraea counts 20 species and 6 hybrids; in the catalog of 2013 there are 17 species, 6 hybrids and 7 forms. The first species that was included into the collections of the Dendropark in 1950 was Spiraea flexuosa Fisch. ex Cambess. During 1956–1965 the collection was replenished with 18 taxa, from 2000 to 2010 – with 1 species and 10 forms. At present it counts 15 species, 5 hybrids and 9 forms, which belong to 4 sections: Glomerati, Chamaedryon, Spiraea, Calospira. Conclusions. The history of the introduction of species of the genus Spiraea of the Dendropark Olexandria collection dates back to the late 1950’s. Plants of all taxa form parterre in park landscape compositions and collections. They have achieved generative development; they are winter-hardy and drought-tolerant. Endemic Spiraea polonica Block., introduced in 2004 from a natural habitat, form an introductive population in the forest phytocenosis of the Dendropark, expanding due to the root growth.